Penurunan Kadar Progesteron Setelah Pemberian PGF 2? Yang Diekstrak Dari Sel Monolayer Vesikula Seminalis Sapi Bali Disimpan Pada Suhu Dan Waktu Berbeda (DECREASE LEVEL OF PROGESTERONE AFTER TREATED WITH PGF 2? EXTRACTED FROM BALI CATTLE VESICULA SEMINAL - Pemayun, Tjok Gde Oka; Trilaksana, I Gusti Ngurah Bagus; Mahaputra, Laba (Buletin Veteriner Udayana, 2015)
The aim of this study was to evaluate the efectiveness of PGF2? on the decrease level of progesterone after treated with PGF2?  that extracted from bali cattle vesicula seminalis monolayercell that stored for 0 month, two months and four months at temperature 40C and -4oC. Sample that used in this study was PGF2? producted from bali cattle vesicula seminalis monolayer cell. Acomplete random sample with two factorial pattern was used i.e; factor I was the period stored (0month, two months, and four months) and factor II was the temperature storage  (4oC).Each treatment was completely with repetitions. Result showed that PGF2? that resulted from balicattle monolayer cell vesikula seminalis that stored for two months was able to decrease level ofprogesterone to 49.06% at -4oC  and 48.82% at temperature 40C. Similarly. The PGF2? that storedfor four months affected on the decrease of progesterone level to 36.33% at temperature -4C and35.81% at temperature 40C. It can be concluded that PGF2? that resulted in the study that stored forfour months at temperature of -40C and 40C may have capability to regress luteal cell.
Keywords: PGF2?; Progesterone; storage viability